2017
DOI: 10.1080/13561820.2017.1329199
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating across the threshold: The development of interprofessional expertise in child safeguarding

Abstract: Collaborating across the threshold: the development of inter-professional expertise in child safeguarding. AbstractThis paper reports on an empirical study of the expertise that different professionals develop in working together to safeguard children. The research involved three key professional groups who work with children: nursing, teaching and social work. The methodology used a clinical scenario and critical incident to explore professional perspectives and experiences of collaboration. Data collection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…The vast majority of the supervisors responded that the course was relevant to professional practice. This is a very positive finding since there is a need for better IPC in kindergartens/schools and the health and welfare services (Anderson, 2013;Power et al, 2013;Hood et al, 2017;Martinussen et al, 2017;GDB 2017SDG Collaborators (2017; Fukkink and van Verseveld, 2019). Some of the present students will not work with children and young people as pupils/students/patients/clients in their future jobs.…”
Section: Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of the supervisors responded that the course was relevant to professional practice. This is a very positive finding since there is a need for better IPC in kindergartens/schools and the health and welfare services (Anderson, 2013;Power et al, 2013;Hood et al, 2017;Martinussen et al, 2017;GDB 2017SDG Collaborators (2017; Fukkink and van Verseveld, 2019). Some of the present students will not work with children and young people as pupils/students/patients/clients in their future jobs.…”
Section: Relevancementioning
confidence: 99%
“…In teacher education programmes, priority is given to three interdisciplinary themes: democracy and citizenship, sustainable development, and public health and well-being (Ministry of Education and Research, 2015). School is an important arena for promoting mental and physical health in children and young people (Hood et al, 2017). However, to the best of our knowledge no large-scaled IPL study has been published including students from both teacher educations, and health and social care study programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Through professional training, they can unravel situations if something is not right with the child in their practices, including finding out if the child is physically harmed or if the child behaves increasingly different from what can be deemed normal or expected from the child. Bell and Singh (2017) and Hood et al (2017) indicated that the probability of an educator recognising abuse or neglect is high.…”
Section: Facilitating the Right To Protection For The Child In Needmentioning
confidence: 99%
“…Both collaborators in the current study found that strengthening collaboration requires training-training of teachers to identify the child in need, but also joint training for a common understanding of the child in need and the helping process. Hood et al (2017) emphasised that as multiple thresholds coexist, it is therefore crucial for the education to incorporate various aspects of interprofessional collaboration. Collaborative learning opportunities during professional education, including practice learning through field placement, would allow educators to teach and supervise in practise collaboration, and provide knowledge and skills concerning how to navigate the process of interdisciplinary collaboration.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…From the 248 articles, 29 were selected for assessment of the full-text eligibility. We subsequently excluded 19 studies from our analysis that did not report empirical findings but were conceptual or were narrative reviews, leaving 10 primary studies [33][34][35][36][37][38][39][40][41][42]; the results of some studies are integrated in the discussion.…”
Section: Search and Selection Of Studiesmentioning
confidence: 99%